Study on the Spontaneous Imbibition Characteristics of the Deep Longmaxi Formation Shales of the Southern Sichuan Basin, China. (14th October 2021) - Qian, Chao; Li, Xizhe; Shen, Weijun; Guo, Wei; Hu, Yong; Li, Zhongcheng
Abstract : Deep shale gas reservoirs are a significant alternative type of shale gas reservoir in China. The productivity of deep shale gas wells is lower than that of shallow shale, and the imbibition characteristics of deep shale have a significant effect on the retention and backflow of fracturing fluid and the productivity of shale gas wells. In this study, the pore structure characteristics of organic-rich deep shale in the Lower Silurian Longmaxi Formation of Weiyuan-Luzhou play were analyzed by low-temperature nitrogen adsorption experiments, and then the imbibition characteristics and factors influencing deep shale were extensively investigated by spontaneous imbibition and nuclear magnetic resonance experiments. The results show that mainly micropores and mesopores are growing in the deep organic-rich shale of the Longmaxi Formation. The spontaneous imbibition curve of deep shale can be divided into an initial spontaneous imbibition stage, an intermediate transition stage, and a later diffusion stage, and the imbibition capacity coefficient of deep shale is lower than that of shallow shale. The transverse relaxation time (T2) spectrum distributions suggest that clay hydration and swelling produce new pores and microcracks, but then some pores and microfractures close. Deep shale reservoirs have an optimal hydration time when their physical properties are optimal. The increasing pore volume and the decreasing TOC content can enhance the imbibition capacity of shale. An inorganic salt solution, especially a KCl solution, has an inhibitory effect on the imbibition of shale. Higher salinity will result in a stronger inhibitory effect. It is crucial to determine the optimal amount of fracturing fluid and soaking time, and fracturing fluid with a high K + content can be injected into the Longmaxi Formation deep shale to suppress hydration. These results provide theoretical guiding significance for comprehending the spontaneous imbibition and pore structure evolution characteristics of deep shale and enhancing methane production in deep shale gas reservoirs.